DEVELOPMENT OF COMMUNICATIVE SKILLS IN CHILDREN OF YOUNGER SCHOOL WITH SEVERE AND MULTIPLE DISORDERS OF DEVELOPMENT USING ELEMENTS OF AQUATERAPY - Хлопин, Ольга; Мочалова, Лариса (SWorldJournal, 2020)
Currently, the number of children in the category of children with disabilities with severe and multiple developmental disabilities has significantly increased in Russia. The help of this category of children is one of the main conditions for the organiza